Effects of Urban Environmental Conditions and Landscape Structure on Taxonomic and Functional Groups of Insects - Vergara-Egert, P; Alaniz-Baeza, A (Elsevier GmbH, 2021)
Insects are a particularly sensitive group to urbanization, and they are also highly dependent on structural, compositional, and environmental characteristics of the landscape as well as its scale. The identification of the landscape variables and scale which influence this group are necessary for the development of sustainable landscape planning in the face of climate change and environmental degradation. Here we aim to determine the most important spatial scale for the diversity of taxonomic and functional groups of insects, testing the hypothesis that the importance of environmental and landscape structure-composition variables on insect diversity and functional groups vary with the spatial scale. Finally, we selected the scale with the highest proportion of explained variance for the total, analyzing the correlations of landscape variables with each group. We collected insects in 15 non-overlapped landscapes, classifying them according to their order and functional groups. We generated 6 concentric circles from a focal patch per landscape, using remote sensing data to characterize landscape environmental and structural-composition variables from 200 to 1200 m. Finally, we tested the hypothesis by using the Variable Importance for the Projection and R2 from Partial Least Square Regressions metrics. We identified that the importance of landscape diversity varied across the different scales. We found that 600 m was the scale with the highest explained variance for orders and functional groups in the total set. The scale at diversity of orders and functional groups reached the highest explained variance diversity that varied among groups. Parasitoids, predators, and phytophages responded to smaller scales, while pollinators and micophages to, and saproxylics to larger scales. Urban area and temperature were negatively associated with total diversity, while variables linked with vegetation quality presented a positive correlation. The generated results may contribute to improve the understanding of the urban ecology of insects, aiming to contribute with sustainable urban planning and conservation. © 2020 Elsevier GmbH